Upaya Menjaga dan Meningkatkan Motivasi Kerja Pegawai Berdasarkan Faktor-Faktor Penyebab Perubahan Motivasi Kerja - Kevin Febrian; Olivia Martha Jacobus (Universitas Sultan Ageng Tirtayasa, 2022)
Work motivation is an aspect that influences the stability of a company, institution or organization. In a company sometimes there are problems of work motivation that involve employees and there are still many companies that do not understand the factors that trigger changes in work motivation of their employees, as well, the efforts that must be made to overcome motivational problems in employees. Therefore, this study was conducted to determine the efforts that companies can do to maintain employee work motivation based on the factors that cause changes in work motivation. The research method that used in this study is a qualitative descriptive research method. The output from the reseach is the form of suggestions for company policy that can be made by company leaders to maintain and improve their employee work motivation.